I have a problem which says Y= 3^log(base2)t I set it up as ln y = log(base2)t (ln 3) I am not sure what to do after this step!
Follow Math Help Forum on Facebook and Google+
Originally Posted by KarlosK I have a problem which says Y= 3^log(base2)t I set it up as ln y = log(base2)t (ln 3) I am not sure what to do after this step! Use the identity .
Originally Posted by KarlosK I have a problem which says Y= 3^log(base2)t I set it up as ln y = log(base2)t (ln 3) I am not sure what to do after this step! You can differentiate implictly given that You will also need to use the change of base rule on
View Tag Cloud